2018
DOI: 10.1039/c8cc01491d
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function and antagonism of semen amyloids

Abstract: Amyloid fibrils are linear polypeptide aggregates with a cross-β structure. These fibrils are best known for their association with neurodegenerative diseases, such as Alzheimer's or Parkinson's, but they may also be used by living organisms as functional units, e.g. in the synthesis of melanin or in the formation of bacterial biofilms. About a decade ago, in a search for semen factors that modulate infection by HIV-1 (a sexually transmitted virus and the causative agent of the acquired immune deficiency syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 102 publications
1
48
0
Order By: Relevance
“…While our study was performed in vitro with seminal plasma‐free sperm, ejaculated sperm bathing with seminal plasma may even have a higher rate of carrying HIV‐1 on their surface. Amyloid fibrils SEVI (Semen‐derived Enhancer of Viral Infection), present in seminal plasma, accelerate the HIV‐1 transport to target cells including sperm . In addition, since sperm can swim upwards in the tract and bind to other epithelial cells (e.g., the endometrium), sperm‐associated HIV‐1 virions are likely able to infect additional epithelial cells in the female reproductive tract.…”
Section: Discussionmentioning
confidence: 99%
“…While our study was performed in vitro with seminal plasma‐free sperm, ejaculated sperm bathing with seminal plasma may even have a higher rate of carrying HIV‐1 on their surface. Amyloid fibrils SEVI (Semen‐derived Enhancer of Viral Infection), present in seminal plasma, accelerate the HIV‐1 transport to target cells including sperm . In addition, since sperm can swim upwards in the tract and bind to other epithelial cells (e.g., the endometrium), sperm‐associated HIV‐1 virions are likely able to infect additional epithelial cells in the female reproductive tract.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the secondary structure and those in the properties of semen amyloids have been reported to be associated with reproductive health and sexually transmitted diseases, such as acquired immune deficiency syndrome (AIDS) . In order to understand the structural determinants of PAP 248‐286 and its C‐terminal domain (CTD), at the molecular level, the interaction of both the peptides with DOPC was assessed by employing CD spectroscopy, and it was confirmed that the interaction of PAP 248‐286 with DOPC does not drive the formation of β‐sheets, indicating inhibition of fibril formation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it led to the discovery of an endogenous CXCR4 antagonist that blocks CXCR4-tropic HIV infection (Zirafi et al, 2015). Moreover, screening a semen derived peptide library identified amyloidforming peptides as enhancers of HIV-1 infection (Münch et al, 2007a;Arnold et al, 2012;Röcker et al, 2018) and antibacterial agents (Easterhoff et al, 2013). Thus, the concept of isolating novel AMPs from body fluids resulted in the identification of peptides that inhibited bacterial and viral infections by novel and unexpected mechanisms.…”
Section: Introductionmentioning
confidence: 99%